Review of the Evaluation of Immigration and Leadership Socialization Activities by Immigration Polytechnic Cadets at SMAN 1 Tanjungpinang - Gede Maha Aditya Pramana; Intan Nurkumalawati (Polteknik Imigrasi, 2020)
The purpose of implementing the Immigration and Leadership Socialization activities at SMAN 1 Tanjungpinang by the Immigration Polytechnic Taruna is to disseminate immigration information and also about the Immigration Polytechnic itself to a wide audience, especially to people who are far from the existence of big cities. The implementation of this socialization is one form of the tri dharma of higher education, namely community service, where cadets provide immigration information that is useful to a wide audience. This outreach activity is one of a series of events for the Immigration Polytechnic Taruna Field Work Practice in the Tanjungpinang area. It is hoped that with this socialization, people, especially the younger generation, will understand more deeply about immigration in their country, about the Immigration Polytechnic and also leadership procedures to produce a quality generation.